The Effect of Flexible Working Arrangement, Work-Life Balance, and Work Environment on Job Satisfaction Startup Employee in Tangerang - Muhammad Rafi Dhia (Jurnal Ekonomi Manajemen Bisnis dan Akuntansi, 2024)
This study investigates the impact of work-life balance, flexible scheduling, and the workplace environment on the job satisfaction of employees at startups in Tangerang. The research focuses on three independent variables flexible work schedules, work-life balance, and the workplace environment and one dependent variable, job satisfaction. Data was collected through questionnaires distributed to 97 employees from Tangerang startups. The study utilized primary data and associative quantitative analysis, employing structural equation modeling (SEM) with Smart PLS. The results indicate that flexible work schedules significantly affect job satisfaction, as shown by a t-statistic of 8.609, which is above the threshold of 1.96, and a p-value of 0.000, which is below the threshold of 0.05. Similarly, work-life balance also has a significant impact on job satisfaction, with a t-statistic of 34.877, far exceeding 1.96, and a p-value of 0.000. Additionally, the work environment has a substantial impact on job satisfaction, evidenced by a t-statistic of 4.424 and a p-value of 0.000, both meeting the significance criteria.